Fragmented powers : confrontation and cooperation in the english-speaking world - Avril, Emmanuelle; Cossu-Beaumont, Laurence; Fée, David; Mourlon, Fabrice; Della Porta, Donatella (Emerald Publishing Limited, 2025)
Against the backdrop of an increasingly unstable and multipolar modern world, this edited collection takes an interdisciplinary approach to explore institutional, political, social and media fragmentation in today's increasingly polarised English-speaking world environment. Taking fragmentation as either conflictive or resulting in cooperation, it evaluates to what extent the changes induced are long-lasting and irreversible. Introducing 20 new case studies which analyse national-level politics, local governance, civil society mobilisation and more, the chapters examine the trajectories of American and British societies. Uncovering both the positive and negative effects of fragmentation, the former materialising in shifts in power away from centralised structures towards private economic actors, citizens and consumers, as well as local authorities, thus allowing for economic innovation, individual freedom and progressive policies, and the latter leading to disunity and the inability to guarantee basic rights, or devise common strategies, maintain stable and functioning economies, and organise effective opposition to state power. Adopting a multi-level approach to exploring the various meanings of fragmentation, chapters cover a variety of political, social, and geopolitical topics. These include fragmented constitutional frameworks and settings; fragmented governance; fragmented political parties; fragmentation in activism and social mobilisation; fragmented cities and urban environments; fragmented public services provision; as well as fragmentation in media and social media. Fragmented Powers is a rich resource for scholars of public policy, urban studies, political science, sociology, international relations, and more.